KINERJA KARYAWAN DITINJAU MELALUI RECRUITMENT, TRAINING, DAN BEBAN KERJA (Study Pada PT Rumpun Sari Kemuning) - Imam Ibrahim (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2020)
Employee performance has an important role in a company, because employees who have good performance will have a positive impact for the company and vice versa, the company would like to have employees who are well performing and able to Accomplish its job well. The purpose of this research is to know the performance of employees are reviewed through recruitment, training, and workload (study at Pt. Rumpun Sari kemuning). The method of analysis used in this study uses quantitative methods and samples of this study as much as 102 people. The results of research that has been done in this study show that simultaneously there is a simultaneous influence between recruitmen, training, and workload positively and significantly impact on employee performance and partially recruitmen, And workloads have a positive and significant impact on employee performance.